How the Nature of an Alpha-Nucleophile Determines a Brønsted Type-Plot and Its Reaction Pathways. An Experimental Study - Campodónico, Paola R.; Tapia, Ricardo A.; Suárez-Rozas, Cristian (Frontiers in Chemistry, 2022)
The reactions between 2-chloro-5-nitro pyrimidine with a serie of α-nucleophile derivatives were kinetically evaluated. The kinetic study was carried out in aqueous media and the data shown an unusual split on the Brønsted type-plot, opening a controversial discussion based on reactivities and possible reaction pathways. These split Brønsted type-plots are discussed over the hypothetical transition state (TS) structures associated to concerted or stepwise mechanisms with emphasis on hydrogen bond interactions between electrophile/nucleophile pair able to determine the reactivities and the plausible reaction routes.